A bio-compatible pyridine–pyrazole hydrazide based compartmental receptor for Al3+ sensing and its application in cell imaging. Issue 37 (2nd September 2021) - Das, Bhriguram; Dolai, Malay; Ghosh, Avijit; Dhara, Anamika; Mahapatra, Ananya Das; Chattopadhyay, Debprasad; Mabhai, Subhabrata; Jana, Atanu; Dey, Satyajit; Misra, Ajay
Abstract : A bio-compatible pyridine–pyrazole hydrazide based chemosensor for Al 3+ has been synthesized and applied for cell imaging studies. Abstract : For practical applications, the development of bio-compatible organic molecules as p-block ion chemosensors is critical. Herein, we report the single crystal (SC) of new pyridine–pyrazole derived Al 3+ sensor H2 PPC [( Z )- N '-(2, 3-dihydroxybenzylidene)-5-methyl-1-(pyridin-2-yl)-1 H -pyrazole-3-carbohydrazide] as well as its Cu-complex SC. The probe exhibits an "off–on" fluorescence response towards Al 3+ ions, and this has been modulated with different solvents. For selective detection of Al 3+ ions, a special coordination pocket in the structural backbone is advantageous. The chemosensor exhibits a submicromolar detection level (LOD = 4.78 μM) for Al 3+ . The density functional theory (DFT) and time-dependent DFT (TD-DFT) calculations of H2 PPC and [Al(HPP)2 ] + (1 ) reveal that a change of the structural conformation of probe H2 PPC upon complexation causes the pyrazole and pyridine units to create a specific cavity to tether Al 3+, and consequently H2 PPC proves to be a promising molecule for Al 3+ detection. Furthermore, the probe has been successfully used to evaluate Al 3+ as a low-cost kit using filter paper strips, and the in situ Al 3+ ion imaging in Vero cells as well as A549 cell lines shows the sensor's nuclear envelope penetrability, indicating that it has great potential for biological and environmental applications.